Antinociceptive and anti-inflammatory activities of Curcumin - de Paz Campos, Marco Antonio (Mexican Journal of Medical Research ICSA, 2013)
Curcumin is a polyphenol derived from the herbal remedy and dietary spice turmeric (Curcuma longa) used by men in the exage as medicinal remedy and spice. In the last decades the curcumin has been an object of multiple studies in vitro and in vivo that have established the scientific bases of their numerous therapeutic activities, emphasizing their powerful anti-inflammatory, anti-cancer and antioxidant properties. In the present work a revision of the anti-inflammatory mechanisms of action is made that include the inhibition of several cell signalling pathways at multiple levels and downregulates cellular enzyme like cyclooxygenase, lipoxygenase and nitric oxide synthase. Also the preclinical and clinical studies that have been carried out in this aspect are mentioned, the support, safety and efficiency of the curcumin used with analgesic and antiinflammatory purposes.